Case report: Additional grounds for tighter regulation? A case series of five women with zolpidem dependence from a Brazilian women-specific substance use disorder outpatient service - Leal, Gabriel; Studart, Igor; Figueiredo, Caio Petrus Monteiro; di Santi, Talita; Suen, Paulo; Brasiliano, Silvia; Hochgraf, Patricia B.; Bacchi, Pedro Starzynski (Frontiers in Psychiatry, 2024)
ObjectiveThis study presents a case series of five women with zolpidem dependence treated at the Drug Dependent Women Treatment Center (PROMUD), one of the first women-specific substance use disorder outpatient services in Latin America.MethodsThis was an retrospective review of medical records of patients with a diagnosis of zolpidem dependence at the Institute of Psychiatry of Clinics Hospital of University of São Paulo between December 2021 and December 2023. Description of the cases followed the Case Report Statement, Checklist and Guidelines (CARE). The weekly zolpidem intake, comprising prescribed amounts and relapse episodes, was totaled to compute a mean daily dose. This was graphically illustrated to bring clinical insights.ResultsThe patients, aged 25-45 years, displayed escalating oral zolpidem doses (range: 60-900 mg/day), with adverse effects such as memory and social impairment, falls, seizures. Commonalities among cases included initiating zolpidem use for primary insomnia and withdrawal symptoms, including rebound insomnia, social impairment, and craving. History of physical and psychological abuse were reported. Comorbid psychiatric conditions, particularly eating disorders (n=3), recurrent depression (n=1), borderline personality disorder traits (n=1), and attention deficit hyperactivity disorder (n=1), were identified. Although zolpidem abuse often correlates with the concurrent abuse of other substances, none of the reported cases in this study exhibited other substance use disorders. Concurrent use of sedatives, especially benzodiazepines and levomepromazine, was observed (n=2).ConclusionThe surge in zolpidem prescriptions, driven by its perceived safety and low abuse potential compared to benzodiazepines, may lead to a global health issue of dependence. The medical community faces the challenge of managing this without standardized treatment protocols. Our case series underscores the effectiveness of the PROMUD program, which employs a multidisciplinary, women-specific approach with tailored group therapies and weekly psychiatric appointments to address and prevent relapse.